Applying Design of Experiments on the Mechanical Properties of Mefenamic Acid-Loaded Transdermal Films - Suksaeree, Jirapornchai; Monton, Chaowalit (Trends in Sciences, 2023)
The Design-Expert® program version 11 was used to analyze and optimize the mechanical properties of mefenamic acid-loaded transdermal films. The dependent variables were ultimate tensile strength (UTS), elongation at break and folding endurance, whereas the independent variables were silicone rubber, mefenamic acid and dibutyl sebacate (DBS). While quadratic models predicted elongation at break and folding endurance more accurately, a linear model predicted the highest correlation relationship for UTS. The design of experiments (DOE) estimated that the optimal silicone rubber, mefenamic acid and DBS ratio would be 5.3:2.5:5.2. By demonstrating that the prediction value of the ratio was more than 4, the model was proved to be suitable for forecasting results inside the design space without the requirement for additional trials. Experimental values of UTS, elongation at break and folding endurance were 6.20 ± 0.50 MPa, 711.22 ± 102.00 % and 857 ± 64 folds, respectively. The percent error was determined to be 8.50, 6.70 and 9.28 %, respectively. The DOE successfully demonstrated a low percent error of prediction (less than 10 %) from the Design-Expert® approach, which was satisfactory and accepted for preparation in drug delivery systems. HIGHLIGHTS Transdermal film formulations containing mefenamic acid had been optimized and enhanced As polymer matrix and plasticizer, silicone rubber and dibutyl sebacate were utilized, respectively While quadratic models predicted more correctly elongation at break and folding endurance, a linear model predicted the greatest correlation relationship for ultimate tensile strength Ultimate tensile strength, elongation at break and folding endurance experimental values were 20 ± 0.50 MPa, 711.22 ± 102.00 % and 857 ± 64 folds, respectively Less than 10 % was successfully demonstrated, which was enough and acceptable GRAPHICAL ABSTRACT